2016
DOI: 10.1016/j.celrep.2016.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Inflammation Redirects Acinar to β Cell Reprogramming

Abstract: Summary Using a transgenic mouse model to express MafA, Pdx1, and Neurog3 (3TF) in a pancreatic acinar cell- and doxycycline-dependent manner, we discovered that the outcome of transcription factor-mediated acinar to β-like cellular reprogramming is dependent on both the magnitude of 3TF expression and on reprogramming-induced inflammation. Overly robust 3TF expression causes acinar cell necrosis resulting in marked inflammation and acinar-to-ductal metaplasia. Generation of new β-like cells requires limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The source of new cells that contribute to the expansion of adult β cell mass during adaptive processes has been debated for several years. Although in vitro and in vivo experiments suggest acinar cells can be converted into β-like cells (19)(20)(21), lineage trace experiments did not support this hypothesis in vivo (22). Adult ductal cells have been suggested to act as precursors of β cells because embryonic ducts are direct precursors of neurogenin 3 + (NGN3 + ) cells, which can give rise to all pancreatic endocrine cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…The source of new cells that contribute to the expansion of adult β cell mass during adaptive processes has been debated for several years. Although in vitro and in vivo experiments suggest acinar cells can be converted into β-like cells (19)(20)(21), lineage trace experiments did not support this hypothesis in vivo (22). Adult ductal cells have been suggested to act as precursors of β cells because embryonic ducts are direct precursors of neurogenin 3 + (NGN3 + ) cells, which can give rise to all pancreatic endocrine cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Pan et al (2013) showed the ability of acinar-to-beta-cell conversion, including an intermediate step with pancreatic multipotent progenitor cells. Clayton et al (2016) performed direct reprogramming of acinar cells on a transgenic mouse by the virus-based induction of PDX1, MAFA, and NGN3. Another important output from their study concerns the impact of inflammation on the reprogramming result.…”
Section: Hb9mentioning
confidence: 99%
“…Proliferative or progenitor-like exocrine cells also may provide clues on regeneration mechanisms in endocrine cells since they are derived from a common progenitor. Furthermore, recent evidence indicates that acinar reprogramming efficiency is significantly reduced upon pancreatic inflammation or hyperglycemia but improved by inhibition of contact-mediated signaling [125] , [130] , [131] , [132] . This highlights the importance of investigating extrinsic factors that potentially hamper or enhance cell conversion in vivo .…”
Section: Approaches Of Endogenous β-Cell Regenerationmentioning
confidence: 99%